Leveraging Technology to Improve Radiology Workflow - Desai, Vishal; Flanders, Adam; Zoga, Adam C. (Seminars in Musculoskeletal Radiology, 2018)
Although advancements in the last decade have automated much of the radiology workflow, there are several areas in the complex imaging process where standardization and innovation can be implemented. We discuss multiple tools and integrations that can help improve operational efficiency, quality, and safety.
Keywords: communication; technology; workflow; value; imaging